Teknik Separasi dan Optimasi Proses Ekstrusi Bungkil Inti Sawit sebagai Bahan Baku Pakan: Optimization of The Separation Method and Extrusion Process of Palm Kernel Cake as Feed Raw Materials - Foni, Lidya Rosa; Sukria, Heri Ahmad; Retnani, Yuli; Risyahadi, Sazli Tutur (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
This study aimed to evaluate separation method to reduce the shells of palm kernel cake (PKC) and to optimize the extrusion process to increase the nutrient utilization. The sieving process was a method of separating two materials that had different sizes, both solid and liquid materials. The extrusion process variables used in this study were extrusion temperature and moisture content of PKC as optimization variables in the response surface methodology (RSM). The RSM design was central composite design (CCD) with 13 treatments and analysed with Design Expert version 13. PKC was separated from its shell by filtering it at a size of ≤0.600 mm and continued the extrusion process for 13 treatments using temperatures starting from 72 to 128 °C and moisture content starting from 22 to 78%. The main variable response was crude protein (CP), crude fibre (CF), and ether extract (EE). Based on statistical analysis, it was found that temperature and moisture content had a significant effect (p<0.05) on the mathematical model of the relationship between the independent variables (temperature and moisture content) and the best CP, CF and EE responses. PKC extrudate had a bulk density value of 420 kg m-3 and a total solubility of 24.11%. The conclusion of this study was that the optimal extrusion treatment at BIS was using 91 °C and 42% moisture content to produce the best chemical and physical qualities. Key words: extrusion, nutritional component, palm kernel cake, physical characteristic, response surface methodology